Pengaruh Citra Merek, Kualitas Produk, dan Kualitas Pelayanan Terhadap Loyalitas - Milasari, Selvi (Jurnal Kompetitif Bisnis, 2021)
This study aims to determine and explain the influence of brand image, product quality and service quality on loyalty to consumers of Sonhaji Sony’s Chicken Meatballs & Noodles in Bandar Lampung. This type of research uses explanatory research with a quantitative approach. The sampling technique in this study is non-probability sampling with a sample of 100 consumers. The data collection technique used a questionnaire with a Likert scale. Based on the results of the research and data analysis conducted, it is known that of the three independent variables, namely brand image, product quality and service quality, the variables that have a partially significant effect on loyalty are the variables of service quality and product quality. While the brand image variable has no significant effect direction to consumer loyalty. The implementation of the results of this study is to improve product quality and service quality at Sonhaji Sony’s Chicken Meatballs & Noodles in order to create consumer loyalty.